mik cảm ơn
\(\sqrt{\frac{3a-4}{-5}}\)
tìmd dkxd của nó
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có: \(\frac{6}{\sqrt{2}-\sqrt{3}+3}\)
\(=\frac{6\left(\sqrt{2}-\sqrt{3}-3\right)}{\left(\sqrt{2}-\sqrt{3}+3\right)\left(\sqrt{2}-\sqrt{3}-3\right)}\)
\(=\frac{6\left(\sqrt{2}-\sqrt{3}-3\right)}{5-2\sqrt{6}-9}\)
\(=\frac{6\left(\sqrt{2}-\sqrt{3}-3\right)}{-4-2\sqrt{6}}\)
\(=\frac{6\left(\sqrt{2}-\sqrt{3}-3\right)}{-2\sqrt{2}\left(\sqrt{2}-\sqrt{3}\right)}\)
\(=\frac{3\left(\sqrt{2}-\sqrt{3}-3\right)\left(\sqrt{2}+\sqrt{3}\right)}{-\sqrt{2}\left(\sqrt{2}-\sqrt{3}\right)\left(\sqrt{2}-\sqrt{3}\right)}\)
\(=\frac{3\sqrt{2}\left(\sqrt{2}+\sqrt{3}\right)\left(\sqrt{2}-\sqrt{3}-3\right)}{2}\)
b) Ta có: \(\left(\frac{4}{\sqrt{5}+1}-\frac{4}{\sqrt{5}-1}\right):\sqrt{3+2\sqrt{2}}\)
\(=\left(\frac{4\left(\sqrt{5}-1\right)}{\left(\sqrt{5}+1\right)\left(\sqrt{5}-1\right)}-\frac{4\left(\sqrt{5}+1\right)}{\left(\sqrt{5}+1\right)\left(\sqrt{5}-1\right)}\right):\sqrt{2+2\cdot\sqrt{2}\cdot1+1}\)
\(=\left(\frac{4\left(\sqrt{5}-1\right)}{4}-\frac{4\left(\sqrt{5}+1\right)}{4}\right):\sqrt{\left(\sqrt{2}+1\right)^2}\)
\(=\left(\sqrt{5}-1-\sqrt{5}-1\right):\left|\sqrt{2}+1\right|\)
\(=-\frac{2}{\sqrt{2}+1}\)(Vì \(\sqrt{2}+1>0\))
\(=-\frac{2\left(\sqrt{2}-1\right)}{\left(\sqrt{2}+1\right)\left(\sqrt{2}-1\right)}\)
\(=-2\left(\sqrt{2}-1\right)\)
\(=-2\sqrt{2}+2\)
1, ĐKXĐ: \(x\ge0;x\ne4\)
2, \(=\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}+2\right)+2\sqrt{x}\left(\sqrt{x}-2\right)-2-5\sqrt{x}}{x-4}\)
\(=\frac{\left(x+3\sqrt{x}+2\right)+\left(2x-4\sqrt{x}\right)-2-5\sqrt{x}}{x-4}\)
\(=\frac{3x-6\sqrt{x}}{x-4}\)
\(=\frac{3\sqrt{x}\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{3\sqrt{x}}{\sqrt{x}+2}\)
\(=\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}+\frac{2\sqrt{x}\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}+\frac{-\left(2+5\sqrt{x}\right)}{x-4}\)
\(=\frac{x+2\sqrt{x}+\sqrt{x}+2+2x-4\sqrt{x}-2-5\sqrt{x}}{x-4}\)
\(=\frac{-6\sqrt{x}+3x}{x-4}=\frac{-3\sqrt{x}\left(2-\sqrt{x}\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{3\sqrt{x}\left(2-\sqrt{x}\right)}{\left(\sqrt{x}+2\right)\left(2-\sqrt{x}\right)}=\frac{3\sqrt{x}}{\sqrt{x}+2}\)
\(\left(2\sqrt{6}-4\sqrt{3}+5\sqrt{2}\right)\cdot3\sqrt{6}\)
\(=2\sqrt{6}\cdot3\sqrt{6}-4\sqrt{3}\cdot3\sqrt{6}+5\sqrt{2}\cdot3\sqrt{6}\)
\(=36-36\sqrt{2}+30\sqrt{3}\)
a/ \(A=\frac{1}{5+2\sqrt{6-x^2}}\)
Có: \(-x^2\le0\)với mọi x
=> \(6-x^2\le6\)
=> \(0\le\sqrt{6-x^2}\le\sqrt{6}\)
=> \(5\le5+2\sqrt{6-x^2}\le5+2\sqrt{6}\)
=> \(\frac{1}{5+2\sqrt{6}}\le\frac{1}{5+2\sqrt{6-x^2}}\le\frac{1}{5}\); với mọi x
=> \(\hept{\begin{cases}maxA=\frac{1}{5}\Leftrightarrow\sqrt{6-x^2}=0\Leftrightarrow x=\pm\sqrt{6}\\minA=\frac{1}{5+2\sqrt{6}}\Leftrightarrow\sqrt{6-x^2}=\sqrt{6}\Leftrightarrow x=0\end{cases}}\)
Vậy:...
b/ \(B=\sqrt{-x^2+2x+4}=\sqrt{-\left(x-1\right)^2+5}\)
Có: \(-\left(x-1\right)^2\le0\)với mọi x
=> \(-\left(x-1\right)^2+5\le5\)
=> \(0\le\sqrt{-\left(x-1\right)^2+5}\le\sqrt{5}\)
=> \(0\le B\le\sqrt{5}\)với mọi x
=> \(\hept{\begin{cases}maxB=\sqrt{5}\Leftrightarrow-\left(x-1\right)^2=0\Leftrightarrow x=1\\minB=0\Leftrightarrow\left(x-1\right)^2=5\Leftrightarrow x=\pm\sqrt{5}+1\end{cases}}\)
Vậy:...
a)Ta có:
\(0\le2\sqrt{6-x^2}\le2\sqrt{6}\)
\(\Leftrightarrow\frac{1}{5}\ge\frac{1}{5+2\sqrt{6-x^2}}\ge\frac{1}{5+2\sqrt{6}}=5-2\sqrt{6}\)
\(\Rightarrow\hept{\begin{cases}MAX\left(A\right)=\frac{1}{5}\\MIN\left(A\right)=5-2\sqrt{6}\end{cases}}\)Dấu "=" xảy ra khi \(\hept{\begin{cases}x=0\left(MIN\right)\\x=\sqrt{6}\left(MAX\right)\end{cases}}\)
\(\sqrt{\frac{3a-4}{-5}}\)
\(\sqrt{\frac{3a-4}{-5}}\ge0\)
\(-5< 0< =>3a-4\le0\)
\(3a\le4< =>x\le\frac{4}{3}\)